(untitled) (Journal of the College of Basic Education, 2022)
In this research, Hermite series method is used to find the convergent numerical solutions, this method is tested on linear Volterra integral equation of the second kind, the result was highly accurate. The algorithm and example is given to explain the solution procedures. The comparison of numerical solutions was compatible with exact solutions.